Enhancement of photo-conversion efficiency of organic solar cells by plasmon resonance effect - Otieno, Francis Otieno (My University, 2016)
Organic Photovoltaic (OPVs) is a promising alternative technology to provide clean and inexhaustible energy due to their excellent optoelectronic properties of the active polymer blends. The organic polymers have low weight, tunable electrical and optical properties besides being relatively insensitive to film imperfections which in the long run enable low-cost high-throughput roll-to-roll processing. However, their photo-conversion efficiency (PCE) and instability to air remains their greatest drawback as these preclude their commercialization. Indeed the highest power-conversion efficiency reported in literature is between 10-12 % compared to their inorganic counterparts (40 %). Therefore there is great need for improvement to make them competitive with grid parity. In this thesis, the major factors limiting the efficiency of organic solar cells such as light absorption, exciton diffusion and dissociation as well as charge collection are investigated and discussed. Despite the high thickness dependent absorption coefficients (>105 cm-1) within the visible spectrum the materials exhibit short exciton diffusion lengths (10-20 nm) which limit the optimal active layer thickness to a few nanometers. Improving optical absorption within this thickness forms the basis of this project. We report the use of surface Plasmons synthesized by both thermal evaporation and Radio Frequency (RF) magnetron sputtering system to tune and enhance optical absorption and scattering using the surface Plasmon resonance effect. The NPs were annealed at various temperatures and for different times to reconstruct and modify their shapes, sizes as well as the inter-particle distance (coverage). Stability is of paramount importance in organic semiconductor devices. Serious degradation in air constrains their applications potential. The study further investigates the mechanisms that determine the stability of organic photovoltaic devices. Our results depict the degradation mechanisms and their circumvention through the use of high mobility pentacene to improve stability.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. Johannesburg, 2015.
Keywords: Photovoltaic cells.; Organic semiconductors.; Solar cells.; Plasmons (Physics)